2017
DOI: 10.1039/c6qo00648e
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of acetylene: polyynes, but not carbyne

Abstract: Polymerization of acetylene in the presence of sterically-hindered endgroups leads to polyynes, but with lengths shorter than by stepwise syntheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The stability of NTWCs with respect to inter-carbyne-chain reactions is of special interest, since such reactions can make polyynes explosive. , Depending on the packing of diacetylene groups, triacetylene groups, or longer polyyne groups in neighboring carbyne chains, 1,4-addition, 1,6-addition, or higher-addition polymerization (Figure a and b) potentially occur . In fact, 1,4-addition polymerization commonly occurs for conjugated diynes, triynes, and tetraynes, and 1,6-addition polymerization has been observed for a specially engineered triyne crystal. , These polymerizations can occur rapidly, and the corresponding heat release can be sufficient to cause an explosion .…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The stability of NTWCs with respect to inter-carbyne-chain reactions is of special interest, since such reactions can make polyynes explosive. , Depending on the packing of diacetylene groups, triacetylene groups, or longer polyyne groups in neighboring carbyne chains, 1,4-addition, 1,6-addition, or higher-addition polymerization (Figure a and b) potentially occur . In fact, 1,4-addition polymerization commonly occurs for conjugated diynes, triynes, and tetraynes, and 1,6-addition polymerization has been observed for a specially engineered triyne crystal. , These polymerizations can occur rapidly, and the corresponding heat release can be sufficient to cause an explosion .…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, because of sp 1 hybridization, carbyne has a much higher energy than graphitic carbons, and some materials containing carbyne chains even explode. 3,27,28 The high reactivity makes carbyne chains prefer to crosslink and degrade into more stable forms. 29−32 Hence, the existence of carbyne and bulk carbyne has long been questioned.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, uncapped cumulenic C n chains (also experimentally observed in inert gas atmosphere [10,11] ) and vinylidene-capped chains have been modelled by DFT computations, showing indeed an almost equalized (cumulenic) geometry (BLA < 0.05 A) together with a non-negligible Raman activity. This paper clearly demonstrated that the structural trend in CC bond lengths is a consequence of the termination in short chains: considering as an example vinylidene groups >CH 2 , the existence of two single CH bonds on the last sp 2 carbons of the chain, implies that this carbon will form a double bond with the next sp carbon and the latter one is forced to form again a double bond with the next atom in the chain and so on, thus obtaining a =C=C=C= cumulenic structure on the sp-carbon chain (see Figure 5) [44,45] . paving the way to a true molecular engineering of CAWs, as discussed in the next section.…”
Section: Carbon Atom Wires As Finite Carbyne-like Systemsmentioning
confidence: 99%
“…[12,13]. Other forms of hybridization have also been observed, such as altering single and triple bonds (polyyne) or altering single and double bonds (polycumulene) with stabilizing molecular complexes at the end of the chains [14,15].…”
Section: Introductionmentioning
confidence: 99%